Trephine Stoma Creation Under Local Anesthesia with Sedoanalgesia - Aksu, Ali; Bozan, Mehmet Bugra; Aksoy, Nurullah; Bozan, Ayse Azak; Kutluer, Nizamettin; Kanat, Burhan Hakan; Böyük, Abdullah (My University, 2019)
Aim: In this paper, we aimed to evaluate the patients who underwent trephine stoma with sedoanalgesia in addition to local anesthesia and to share\rthe results.\rMethod: The patients who underwent trephine stoma with sedoanalgesia in addition to local anesthesia for fecal diversion in our general surgery clinic\rbetween June 2012 and June 2017 were evaluated retrospectively. The patients were evaluated in terms of demographic characteristics, diagnosis of\rprimary disease and complications.\rResults: A total of 11 patients (F/M: 4/7) were evaluated. The mean age was 54 (±4) years. The mean follow-up period was 18 months (range 2-30).\rPrimary disease was rectal cancer in seven patients (63.6%), Fournier’s disease in two patients (18.2%), genital cancer in one patient (9.1%), and\rrectovaginal fistula in one patient (9.1%). Only one patient underwent transverse colostomy and 10 patients underwent sigmoid colostomy. There\rwere no complications related to surgical procedures. One patient died on the 14th postoperative day because of complications secondary to metastasis.\rConclusion: Trephine stoma technique, which does not require laparotomy, is a fast, reliable, and easy to use method especially in high-risk patients\rwith poor general condition
Keywords: Genel ve Dahili Tıp; Onkoloji; Cerrahi